2016
DOI: 10.1080/15384101.2016.1152430
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NEK2 as a promising therapeutic approach for cancer treatment

Abstract: Never in Mitosis (NIMA) Related Kinase 2 (NEK2) plays a key role in regulating mitotic processes, including centrosome duplication and separation, microtubule stabilization, kinetochore attachment and spindle assembly checkpoint. NEK2 is aberrantly overexpressed in a wide variety of human cancers and has been implicated in various aspects of malignant transformation, including tumorigenesis, drug resistance and tumor progression. The close relationship between NEK2 and cancer has made it an attractive target f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 96 publications
(145 reference statements)
2
115
0
Order By: Relevance
“…NEK2 overexpression is associated with tumorigenensis, tumor progression, drug resistance and predicts poor prognosis [18, 19]. Several preclinical studies using RNA interference targeting NEK2 have shown the efficient anti-tumor effect against different type of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…NEK2 overexpression is associated with tumorigenensis, tumor progression, drug resistance and predicts poor prognosis [18, 19]. Several preclinical studies using RNA interference targeting NEK2 have shown the efficient anti-tumor effect against different type of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has documented that NEK2 is an important carcinoma biomarker for prognosis and serves as a therapeutic target . A recent report showed that NEK2 ectopic expression not only promotes hepatocellular cancer progression, but also activates drug resistance independent of protein phosphatase‐1/protein kinase B and Wnt/ÎČ‐catenin pathway activation .…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of cancers, NEK2 is aberrantly expressed and is associated with drug resistance and poor prognosis . Recent studies have indicated that NEK2 represents a promising therapeutic target for cancer treatment . For instance, in a previous study, miR‐128 played an essential role in inhibiting colorectal cancer cell proliferation by regulating NEK2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that many SAC components that are activated by incomplete attachment of microtubules to kinetochores, and kinetochore factors (BUB1, CENPL, CEP152, NUF2, SPC24, SPC25, NEK2, INCENP, SGO1L, MLF1IP, CASC5, NDC80, and ASPM), are all highly overexpressed in MDR canines ( Supplemental Tables S2 and S3). Elevated expression of SAC and kinetochore components (NCAPG, NCAPG, SKA3, AURKB, NEK2) is associated with cancer [50][51][52][53][54][55], and is consistent with APC impairment.…”
Section: To Normal Controlsmentioning
confidence: 99%